2017
DOI: 10.12968/denu.2017.44.5.459
|View full text |Cite
|
Sign up to set email alerts
|

Dual role of subepithelial connective tissue grafting in regeneration of periodontal attachment apparatus

Abstract: Periodontal plastic and aesthetic surgery are gaining significant momentum owing to the increasing aesthetic demands by patients. Along with the fulfilment of aesthetic needs, it is imperative that clinicians also enhance function. From these two important viewpoints, subepithelial connective tissue grafting remains an optimum treatment choice for periodontists when treating gingival recession defects accompanied by periodontal attachment apparatus breakdown. Clinical relevance: Subepithelial connective tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Some authors have suggested that osteoprecursor cells in the connective tissue may be activated by grafting procedures, resulting in osteogenesis. [ 30 ] (2) Multiple case reports have reported newly formed bone following connective tissue grafting on the root surface [ 8 10 ]. The authors indicated that a thick gingival graft can be used as a biological membrane to create space between the root surface and gingiva.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that osteoprecursor cells in the connective tissue may be activated by grafting procedures, resulting in osteogenesis. [ 30 ] (2) Multiple case reports have reported newly formed bone following connective tissue grafting on the root surface [ 8 10 ]. The authors indicated that a thick gingival graft can be used as a biological membrane to create space between the root surface and gingiva.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research on whether grafting prevents periodontal recession by reducing the inflammatory response or promoting local osteogenesis is still lacking. Minimal new bone formation parallel to the root surface after soft tissue grafting has been reported in few cases [6][7][8][9][10]. However, there is a lack of case series that have verified the occurrence of osteogenesis, and the osteogenic mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…This material is significant source of inflammatory cells, proteins, like fibrin, vitronectin, fibrin, adhesion molecules and epithelial growth factors [19] all these molecules are involved in modulation of the tissue reparation [1]. In the same direction, advances in basic research provided new compounds that are considerate the second generation of the platelet concentrates [15]. One of them is called Plasmarich fibrin (PRF) [8].…”
Section: Discussionmentioning
confidence: 99%
“…Its migration beyond the boundaries of the cementum enamel junction, exposing the root of the tooth, is called Gingival Recession (GR) which causes functional and aesthetic disturbances to the affected individuals [20]. This condition substantially increases susceptibility to root caries, dentin sensitivity, and causes aesthetic discomfort [15].…”
Section: Introductionmentioning
confidence: 99%
“…As part of the periodontal tissue, the gingiva plays an important role in maintaining the appearance of the teeth and protecting the tooth surface. Contraction of the gingiva increases the space between teeth, sensitivity of teeth, susceptibility to cervical caries, and other adverse consequences [ 4 6 ]. It has been reported that the prevalence of gingival recession in patients with teeth that exhibit low occlusal function is higher than that in patients that exhibit normal occlusion, due to the lack of appropriate occlusal stimulation.…”
Section: Introductionmentioning
confidence: 99%